The economic value of personal protective equipment for healthcare workers. - Theodore Bolas; Kalin Werner; Sarah Alkenbrack; Manuela Villar Uribe; Mengxiao Wang; Nicholas Risko (PLOS Global Public Health, 2023)
In this paper, we examine the cost effectiveness of investment in personal protective equipment (PPE) for protecting health care workers (HCWs) against two infectious diseases: Ebola virus and methicillin-resistant Staphylococcus aureus (MRSA). This builds on similar work published for COVID-19 in 2020. We developed two separate decision-analytic models using a payer perspective to compare the costs and effects of multiple PPE use scenarios for protection of HCW against Ebola and MRSA. Bayesian multivariate sensitivity analyses were used to consider the uncertainty surrounding all key parameters for both diseases. We estimate the cost to provide adequate PPE for a HCW encounter with an Ebola patient is $13.04, which is associated with a 97% risk reduction in infections. The mean incremental cost-effectiveness ratio (ICER) is $3.98 per disability-adjusted life year (DALY) averted. Because of lowered infection and disability rates, this investment is estimated to save $132.27 in averted health systems costs, a financial ROI of 1,014%. For MRSA, the cost of adequate PPE for one HCW encounter is $0.88, which is associated with a 53% risk reduction in infections. The mean ICER is $362.14 per DALY averted. This investment is estimated to save $20.18 in averted health systems costs, a financial ROI of 2,294%. In terms of total health savings per death averted, investing in adequate PPE is the dominant strategy for Ebola and MRSA, suggesting that it is both more costly and less clinically optimal to not fully invest in PPE for these diseases. There are many compelling reasons to invest in PPE to protect HCWs. This analysis examines the economic case, building on previous evidence that protecting HCWs with PPE is cost-effective for COVD-19. Ebola and MRSA scenarios were selected to allow assessment of both endemic and epidemic infectious diseases. While PPE is cost-effective for both conditions, compared to our analysis for COVID-19, PPE is relatively more cost-effective for Ebola and relatively less so for MRSA. Further research is needed to assess shortfalls in the PPE supply chain identified during the COVID-19 pandemic to ensure an efficient and resilient supply in the face of future pandemics.